Pengaruh dimensi komitmen organisasional terhadap kinerja pegawai pada Dinas Pendidikan Kota Jambi - Dahliyanti, Dyta; Jaya, Indra; Rosita, Sry (Jurnal Dinamika Manajemen, 2019)
The purpose of this study was to reveal the influence of the dimensions of affective commitment, continuance commitment, and normative commitment on employee performance. The research method used in this research is the survey method, while data collection techniques are carried out through questionnaires. The population in this study were all civil servants at the Jambi City Education Office. A sample of 60 respondents. The analytical tool used in this study consists of validity and reliability testing, multiple linear regression analysis, t-test, F test, and determination test coefficient test. The entire investigation was calculated using the SPSS version 17.00 program. Research shows that the dimensions of affective commitment, continuance commitment, and normative commitment simultaneously have a positive and significant effect on employee performance. While partially variables that influence employee performance, practical dedication, continuance commitment, and normative commitment. Furthermore, from the three influential dimensions, the dimension of continuance commitment has the most dominant influence.